Pengaruh Latihan Power Otot Tungkai Terhadap Kecepatan Lari Gawang 110 Meter Atlet PASI Lombok Timur - Mahfuz, Mahfuz; Afrian, Herman; Daniyantara, Didik; Hariadi, Hariadi; Nopiana, Rina; Erpan Sryadi, Lalu; Husni Tamim, Muhammad; Hariadi , Nopi; Darmawan, Ilham Nurkholis (Universitas Hamzanwadi, 2024)
This study aims to determine the effect of leg muscle power training on 110 meter running speed. This research is experimental research using a one group pretest posttest design model. The subjects in this research were 7 athletes. The data collection technique used a 110 meter hurdles test and data analysis was pretest posttest one group. The average pretest score was 17.99. Meanwhile, the posttest score obtained an average score of 17.18. The results of the distribution normality test for the pretest and posttest gave the pretest results for the 110 meter hurdles with a normal sig distribution. 0.2 > 0.05, while for the posttest sig. 0.087 > 0.05. This means that the variable speed for running the 110 meter hurdles is normally distributed, because the significance value is > 0.05. The homogeneity results are declared homogeneous because from the test results using the homogeneity test the significance variance is > 0.05. From the paired sample test table it can be seen that the calculated T is equal to 2.3 with a probability value (sig) = 0.061 and a significance level value (α) of 0.05. Because the probability value is 0.061 > 0.05, then Ho is accepted. Thus, it can be concluded in this study that there is a significant influence between leg muscle power training on the 110 meter hurdles speed of PASI East Lombok athletes.